The Influence of Financial Literacy, Debt and Financial Management on Financial Well-Being of Working Individuals - Norwani, Norlia Mat; Muhamad, Nur Aina Nadiah; Yusof, Rohaila; Daud, Wan Mohd Nazri Wan; Zain, Zakiyah (International Journal of Psychosocial Rehabilitation, 2020)
–This study aims to determine the influence of financial literacy, financial management, debt and demographic factors (gender, age and education) on financial well-being of individuals working in Perak, Kedah and Federal Territory of Kuala Lumpur and Putrajaya. The states are selected based on average income of working individuals (high and low average income). Data was collected through google form questionnaire to individuals working in these states. A total of 403 responses are used for data analysis. Two hypotheses are examined: i) Financial literacy and demographic factors influence on financial management and ii) Financial literacy, financial management, debt and demographic factors influence on financial well-being. Multiple regression is used to investigate the influence of the independent variables on the dependent variables. The findings show that only age and education explain financial management while financial management, debt and age significantly contribute in explaining financial well-being. Financial literacy was reported as an influencing factor towards financial management and financial well-being in many research, but no statistical significance is found in this study. This may be an indicator of the need for a more comprehensive financial literacy training for workers or specific modules can be designed at secondary or tertiary levels to ensure everyone learns adequate financial knowledge. These findings can be the basis for policy makers in introducing a comprehensive financial education planning through government and non-governmental organizations such as Ministry of Education, the Counselling and Credit Management Agency (AKPK) and employers. Good financial knowledge will enable individuals to play their role effectively in the increasingly challenging economic environment of the country.